Mise Au Point Des Techniques De Micropropagation Pour Une Multiplication Massive De Gladiolus Segetum Et Gladiolus Dubius - El Chaieb, Emna; Haouala, Faouzi (European Scientific Journal, ESJ, 2016)
Apical buds of corms of gladiolus (Gladiolus segetum and Gladiolus dubius) were cultivated on Murashige and Skoog (1962) medium supplemented with IBA 0.1 mg.l-1 and BA 2 mg.l-1. The number of newly formed buds was 3,8 and 4,13 buds per explants for respectively Gladiolus segetum and Gladiolus dubius. The in vitro Rooting need a supplement with auxin and sucrose. Rooting is not present in the control medium. The rate of rooting varied from 10 to 36%, depending on the species and the concentration of IBA in the medium. The Important rooting (36%) is observed for Gladiolus segetum in the presence of IBA 1 mg.l -1. Finally, the acclimatization is possible, these shoots rooted have formed many corms after 6 weeks of culture.